2012
DOI: 10.6061/clinics/2012(08)09
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic nephrectomy for xanthogranulomatous pyelonephritis – Are there predictive factors for success?

Abstract: OBJECTIVES:Laparoscopic nephrectomy for xanthogranulomatous pyelonephritis is currently associated with great operative difficulty and surgical complications. Herein, we report on our single-center experience and describe predictive factors for successfully accomplishing this procedure.METHOD:Between March 1998 and April 2010, 66 patients (27 men and 39 women) underwent laparoscopic nephrectomy for the treatment of a unilateral nonfunctioning kidney. These patients had previous diagnoses of renal chronic infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Lima et al . [ 8 ] in 2012, in the largest series for reported for XGN of 66 patients have reported a conversion rate of 12.1%. Conversions were found to be due to technical difficulty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lima et al . [ 8 ] in 2012, in the largest series for reported for XGN of 66 patients have reported a conversion rate of 12.1%. Conversions were found to be due to technical difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Benign indications include nephrolithiasis, renal dysplasia, pelvi-ureteric junction (PUJ) obstruction, chronic pyelonephritis, tuberculosis, vesicoureteric reflux, ureterocele, polycystic kidney, and xanthogranulomatous pyelonephritis (XGN). [ 6 7 8 9 10 11 12 ] Although literature supports improved learning curves and outcomes[ 13 14 ] compared to early 1990s,[ 15 ] laparoscopic nephrectomy is still not well established for benign cases. With the reporting of improved results,[ 16 17 18 ] we hereby present our experience.…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al. [22] found that the time to control renal vessels (32±18 min), renal length greater than 12 cm and right-sided nephrectomy were some predictive factors associated with a higher conversion rate in laparoscopic approach. In our cohort, there were six cases of XGP, with only one conversion, one severe intraoperative complication (diaphragmatic perforation) and no postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for LN include nephrolithiasis, renal dysplasia, pelvi-ureteric junction obstruction, chronic pyelonephritis, tuberculosis, vesicoureteric reflux, ureterocele, polycystic kidney, and xanthogranulomatous pyelonephritis. [1][2][3][4][5][6] Ipsilateral LN has been reported in patients with a history of surgical intervention. Turna et al 7 reported the feasibility of laparoscopic partial nephrectomy after previous ipsilateral renal surgery; furthermore, Aminsharifi and Goshtasbi 8 reported that the difficulties associated with LN were similar for patients with previous percutaneous nephrolithotomy compared with those with previous open renal surgery.…”
Section: Introductionmentioning
confidence: 99%